The Climate Citizens’ Assembly of Mallorca: Assessment of the process and impact on the media and public policies. - Ganuza-Fernández, Ernesto; Fernández-Martínez, José Luis; Lancha-Hernández, Emma; Font-Fábregas, Joan; Bates, Coco (My University, 2024)
The Climate Citizens' Assembly of Mallorca (MCA) is the first assembly held in Spain set up by members of civil society. The assembly began on November 19th, 2022 and ended on February 14th, 2023. This report presents the results of the evaluation of the MCA focusing on three dimensions: process evaluation, impact evaluation and digital media impact evaluation.
Keywords: Cambios climáticos; Democracia directa; Participación social; Movimiento ecologista; Citizens' Assembly